Anatomy of the Anterior Half of the Willis Circle through 256-channel Computed Tomography Images Nguyen Tuan Son1, Ngo Xuan Khoa2, Nguyen Quoc Dung3, Mac Dang - Sơn, Nguyễn Tuấn; Hoa, Ngo Xuan; Dung, Nguyen Quoc; Tuan, Mac Dang; Son, Nguyen Phuc; Manh, Pham Hung (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 34 No 2DO - 10.25073/2588-1132/vnumps.4130, 2018)
Abstract: The paper studies the anatomy index of the anterior half of the Willis circle and anatomical variants using 256-channel computed tomography images. The method of convenient sample size 101 was used in the current retrospective cross-sectional study. The study results show that the display of A1 arterior cerebral artery was 97.5%; the display of anterior communicating artery was 81.2%; the display of M1 segment of the middle cerebral artery was 99.5%; the length and width of the A1L (left) sections were 2.46 ± 0.46 and 16.90 ± 2.90; A1R (right): 2.20 ± 0.51 and 16.86 ± 2.90; and the length and width of the anterior communicating artery were 1.61 ± 0.68 and 2.93 ± 1.38. The study also identified four groups of seven species with 40 variants in diameter; a group of two types with six variants of the pre-polygon shape Willis. The study concludes that the 256-channel computed tomography images of the anterior half of the Willis circle fully displayed the index of common anatomy and anatomical variants. Keywords:   Abstract: The paper studies the anatomy index of the anterior half of the Willis circle and anatomical variants using 256-channel computed tomography images. The method of convenient sample size 101 was used in the current retrospective cross-sectional study. The study results show that the display of A1 arterior cerebral artery was 97.5%; the display of anterior communicating artery was 81.2%; the display of M1 segment of the middle cerebral artery was 99.5%; the length and width of the A1L (left) sections were 2.46 ± 0.46 and 16.90 ± 2.90; A1R (right): 2.20 ± 0.51 and 16.86 ± 2.90; and the length and width of the anterior communicating artery were 1.61 ± 0.68 and 2.93 ± 1.38. The study also identified four groups of seven species with 40 variants in diameter; a group of two types with six variants of the pre-polygon shape Willis. The study concludes that the 256-channel computed tomography images of the anterior half of the Willis circle fully displayed the index of common anatomy and anatomical variants. Keywords: The Willis circle, cerebral artery, cerebral angiography. References: [1] Hoàng Minh Tú (2011), “Nghiên cứu biến đổi giải phẫu mạch máu não trên hình ảnh MSCT 64”, Luận văn Thạc sỹ y học, Đại học Y Hà Nội, tr. 6-107. [2] Smita B. Shinde, G. A. Shroff (2016), “Anatomical variations in anterior cerebral artery in human cadaver”, International Journal of Anatomy and Research, 2016, Vol 4(2), pp.2269-72; [3] Michelle Stephanie Jiménez-Sosa (2017), “Anatomical Variants of Anterior Cerebral Arterial Circle. A Study by Multidetector Computerized 3D Tomographic Angiography”, Int. J. Morphol, 35(3), pp. 1121-1128. [4] Cihad Hamidi, Yas ar Bu kte, Salih Hattapog lu(2013), “Display with 64-detector MDCT angiography of cerebral vascular variations”, Surg Radiol Anat, 35, pp.729–736; [5] Masatou Kawashima (2005), “Microsurgical anatomy of cerebral revascularization. Part I: Anterior circulation”, J Neurosurg, 102, pp.116–131. [6] SB Pai, RN Kulkarni, RGVarma(2005), “Microsurgical anatomy of the anterior cerebral artery – anterior communicating artery complex: An Indian study”, Neurology Asia,10, pp.21 – 28. [7] Hartkamp, M.J., et al(1999). "Circle of Willis collateral flow investigated by magnetic resonance angiography." Stroke30(12), pp: 2671-8. [8] Li, Q., et al (2011). "A multidetector CT angiography study of variations in the circle of Willis in a Chinese population." J Clin Neurosci18(3), pp: 379-83.